ANALISIS DAYASAING JAGUNG DI WILAYAH SENTRA PRODUKSI DI INDONESIA DENGAN PENDEKATAN POLICY ANALYSIS MATRIX (PAM) (Forum Agribisnis, 2019)
The objectives of this research are to analyze competitiveness and the impact of government’s policy of maize farming in several central productions in Indonesia. This research was conducted to analyze maize competitiveness using PAM (Policy Analysis Matrix) method. Data sample was conducted at four maize production centers, including East Java, Central Java, West Java, and South Sulawesi. The results show the forth centre have competitiveness. This showed by PCR values in some production areas less than 1 and for competitive advantage, indicated by DRCR values in production areas also less than 1. Analysis of the Government policy aspect, the government has been able to provide positive incentives for maize farming in North Jawa, Centre of Jawa and West Java. The impact of government policy on inputs and outputs simultaneously can provide a positive incentive to farmers at maize production sites in Java. But the government’s policy hasn’t been able to provide for output in Sulawesi Selatan.  The conclusion is the fourth centres of maize production have competitive and comparative advantage. Sulawesi Selatan has high comparative advantages, so Sulawesi Selatan has high  potential to improve maize farming.